Vaginally administered PEGylated LIF antagonist blocked embryo implantation and eliminated non-target effects on bone in mice. - Ellen Menkhorst (Public Library of Science (PLoS), 2011)
Female-controlled contraception/HIV prevention is critical to address health issues associated with gender inequality. Therefore, a contraceptive which can be administered in tandem with a microbicide to inhibit sexually transmitted infections, is desirable. Uterine leukemia inhibitory factor (LIF) is obligatory for blastocyst implantation in mice and associated with infertility in women. We aimed to determine whether a PEGylated LIF inhibitor (PEGLA) was an effective contraceptive following vaginal delivery and to identify non-uterine targets of PEGLA in mice.Vaginally-applied (125)I-PEGLA accumulated in blood more slowly (30 min vs 10 min) and showed reduced tissue and blood retention (24 h vs 96 h) compared to intraperitoneal injection in mice. Vaginally-applied PEGLA blocked implantation. PEGLA administered by intraperitoneal injection inhibited bone remodelling whereas vaginally-applied PEGLA had no effect on bone. Further, PEGLA had no effect in an animal model of multiple sclerosis, experimental auto-immune encephalomyelitis, suggesting PEGLA cannot target the central nervous system.Vaginally-administered PEGLA is a promising non-hormonal contraceptive, one which could be delivered alone, or in tandem with a microbicide. Vaginal application reduced the total dose of PEGLA required to block implantation and eliminated the systemic effect on bone, showing the vagina is a promising site of administration for larger drugs which target organs within the reproductive tract.